The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/brb3.2320
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies, optimism, and resilience factors associated with mental health outcomes among medical residents exposed to coronavirus disease 2019 in Qatar

Abstract: The aim of this study is to examine the association between coping strategies, resilience, optimism and different mental health outcomes like stress, anxiety, and depression among the medical residents' during the COVID-19 pandemic, with consideration of different factors like seniority, frontliner, gender, and coping style.Methods: An electronic survey was sent to all medical residents in Qatar. Depression, anxiety, and stress were assessed by the DASS-21. Professional quality of life was measured by the ProQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 40 publications
2
24
1
2
Order By: Relevance
“…Current findings suggests that maladaptive coping displayed a negative association whith optimism, whereas adaptive coping displayed a positive association whith optimism. This result aligns with our hypothesis and previous research ( Leslie-Miller et al, 2021 ; Smida et al, 2021 ). Individuals who were motivated to deal with COVID-19 displayed higher so cews in optimism and positive anticipation ( Leslie-Miller et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Current findings suggests that maladaptive coping displayed a negative association whith optimism, whereas adaptive coping displayed a positive association whith optimism. This result aligns with our hypothesis and previous research ( Leslie-Miller et al, 2021 ; Smida et al, 2021 ). Individuals who were motivated to deal with COVID-19 displayed higher so cews in optimism and positive anticipation ( Leslie-Miller et al, 2021 ).…”
Section: Discussionsupporting
confidence: 94%
“…Individuals who were motivated to deal with COVID-19 displayed higher so cews in optimism and positive anticipation ( Leslie-Miller et al, 2021 ). A clear set of adaptive coping skills, including how to think optimistically and how to approach problems and adverse events, has been shown to help workers deal with psychological distress ( Smida et al, 2021 ). Hence, individuals making reasonably realistic appraisals of problems and planning the future, and trying to prevent adverse effects of existing events may provide guidance to a more positive view of the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sub-theme Prevention Strategies discusses the frontliners' strategy to avoid any negative behavior that will affect their work. Smida et al (2021) specified that gaining the skill of optimism can assist in confronting stress or setback, can help to overcome failure in particular events, and strengthens self-efficacy and resilience. The participants revealed that they had to deal with the unruly behavior and compulsive attitude of the patients in their workplace, but frontliners prevented this by showing more patience and by just taking time to rest.…”
Section: Coping Strategiesmentioning
confidence: 99%